Psychosexual Correlates of Sexual Double Standard Endorsement in Adolescent Sexuality - Emmerink, Peggy M. J. (J Sex Res, 2016)
Endorsement and enactment of the (hetero)sexual double standard (SDS), prescribing sexual modesty for girls and sexual prowess for boys, has been shown to be negatively related to sexual and mental health. To be able to challenge the SDS, more insight is needed into the conditions that shape gendered sexual attitudes. A survey was conducted among 465 heterosexual adolescents (aged 16–20 years), examining the relationship between a number of relevant demographic and psychosexual variables and SDS endorsement. SDS endorsement was assessed using a newly developed instrument, the Scale for the Assessment of Sexual Standards Among Youth (SASSY). Gender (being male) and religiousness were significantly associated with increased SDS endorsement. For both boys and girls, increased feelings of entitlement to self-induced sexual pleasure (e.g., masturbation) were significantly associated with reduced SDS endorsement, whereas higher gender investment was significantly associated with increased SDS endorsement. Furthermore, increased feelings of entitlement to partner-induced sexual pleasure and more frequent talking about sexuality with peers were associated with increased SDS endorsement among boys but not among girls. We conclude that future research should explore peer influence processes through peer communication about sex, gender investment, and feelings of entitlement to both self and partner-induced sexual pleasure.